Menumbuhkan Kecerdasan Spiritual Pada Anak Usia Dini Melalui Kisah-Kisah Tauladan di Masa New Normal - Lailatul Kasanah; Siti Mufarochah (Program Studi Pendidikan Islam Anak Usia Dini, 2021)
The pandemic period teaches teachers to continue to guide and teach with the aim that early childhood development can be optimal both physically and psychologically, Children are the greatest deposit given by the creator, therefore early childhood also has extraordinary intelligence, there are 3 intelligences that possessed by children, namely brain intelligence (IQ), emotional intelligence (EQ), and spiritual intelligence (SQ). but spiritual intelligence that makes children able to balance the three intelligences. Spiritual intelligence is intelligence that makes a person whole, because there is a conscience that will guide him. There are many ways that can be done so that children can increase their spiritual intelligence, including telling all the role models that our religion has, especially stories about the prophet Muhammad. The giving of this example is done online